Sensory Characteristics and Volatile Components of Dry Dog Foods Manufactured with Sorghum Fractions - Di Donfrancesco, Brizio (Molecules, 2017)
Descriptive sensory analysis and gas chromatography-mass spectrometry (GC-MS) with a modified headspace solid-phase microextraction (SPME) method was performed on three extruded dry dog food diets manufactured with different fractions of red sorghum and a control diet containing corn, brewer’s rice, and wheat as a grain source in order to determine the effect of sorghum fractions on dry dog food sensory properties. The aroma compounds and flavor profiles of samples were similar with small differences, such as higher toasted aroma notes, and musty and dusty flavor in the mill-feed sample. A total of 37 compounds were tentatively identified and semi-quantified. Aldehydes were the major group present in the samples. The total volatile concentration was low, reflecting the mild aroma of the samples. Partial least squares regression was performed to identify correlations between sensory characteristics and detected aroma compounds. Possible relationships, such as hexanal and oxidized oil, and broth aromatics were identified. Volatile compounds were also associated with earthy, musty, and meaty aromas and flavor notes. This study showed that extruded dry dog foods manufactured with different red sorghum fractions had similar aroma, flavor, and volatile profiles.